The future of computing Computing. China aims for primacy in technology. IN The New York Times. - Barboza, David; Markoff, John.
What's next? If we had a supercomputer that could predict the future, we would tell you. But if the past is any guide, the prediction would certainly be wrong. Here are some technologies that are changing the world.
Keywords: Technological innovations; Internet -- China; Tianhe-1A Supercomputer